منطق التدرج في مصادر التمويل لدى المؤسسات الصغيرة الابتكارية - خونــي, د/ رابـح; حريــد, رامـي (Sciences humaines, 2015)
تتميـز المؤسسات الصغيرة الابتكارية عن باقي المؤسسات بمجموعة من الخصائص أهمها شدة المخاطر وعدم تماثل المعلومات بين ملاكها المسيرين والبنوك. هذه الخصائص لها تأثير كبير على التفضيلات المالية للمؤسسات الصغيـرة الابتكارية، كونها تفرض عليها الأخذ بأولويات تختلف عن تلك التي تنـص عليها  نظريـة سلم الأولويات. الكلمات المفتاحية : المؤسسات الصغيرة الابتكارية، شدة المخاطر، عدم تماثل المعلومات، التفضيلات المالية، نظرية سلم الأولويات. The innovative small firms differ from other firms through many characteristics such as the extent of dangers, asymmetry of information between their owners-managers and banks. These characteristics have a dominant impact on the financial preferences of the innovative small firms, imposing on it taking priorities which are different from those stipulated by the peaking order theory. KEY-WORDS : innovative small firms, extent of dangers, asymmetry of information, financial preferences, Pecking order theory.